Clinical Assessment of Child and Adolescent Personality and Behavior - Frick, Paul J.; Barry, Christopher T.; Kamphaus, Randy W. (Springer, 2010)
Psychologists offer an increasing variety of services to the public. Among these services, psychological assessment of personality and behavior continues to be a central activity. One main reason is that other mental health professionals often do not possess a high level of competence in this area. When one views psychologists who serve children and adolescents, psychological, assessment seems to take on an even greater role. It follows, then, that comprehensive and enlightened graduatelevel instruction in assessment should be a high priority for educators of psychologists who are destined to work with youth. This book is an outgrowth of our efforts to improve our own instruction of child and adolescent assessment skills. We found that existing textbooks were not serving us well. Most of them were encyclopedic, edited volumes that were (1) uneven in the quality across chapters and/or (2) not geared either in format or level of presentation for beginning graduate instruction. The few single- or co-authored volumes available tended to lack the breadth of coverage we deemed necessary. Some focused largely on theoretical issues related to psychological testing, with minimal discussion of practical applications and use of specific tests. Others focused solely on summaries of individual tests, without reviewing the theoretical or empirical context within which to use the tests appropriately